Pain catastrophizing hinders Disease Activity Score 28 – erythrocyte sedimentation rate remission of rheumatoid arthritis in patients with normal C‐reactive protein levels. (26th October 2021) - Yoshida, Tamami; Hashimoto, Motomu; Horiguchi, Go; Murakami, Kosaku; Murata, Koichi; Nishitani, Kohei; Watanabe, Ryu; Yamamoto, Wataru; Tanaka, Masao; Morinobu, Akio; Ito, Hiromu; Matsuda, Shuichi; et al.
Abstract: Aim: This study aimed to assess the relationship between pain catastrophizing and achievement of 28‐joint Disease Activity Score‐defined remission of rheumatoid arthritis (RA), considering the presence or absence of systemic inflammation, and to evaluate associated factors for pain catastrophizing. Method: This cross‐sectional study included 421 RA outpatients. The relationship between pain catastrophizing and remission was analyzed by adjusting several confounding factors. Univariable and multivariable analyses were performed to determine the relationship between pain catastrophizing and RA‐related factors, comorbidities, and lifestyle habits. Results: The prevalence of pain catastrophizing was 26%. Pain catastrophizing was negatively associated with remission (odds ratio 0.62, 95% confidence interval 0.38‐1.00, P = .048). A multinomial logistic analysis showed that the presence of pain catastrophizing was an independent factor that was negatively correlated with the achievement of remission in the absence of systemic inflammation (odds ratio 0.51, 95% confidence interval 0.28‐0.93, P = .029). Factors associated with elevated ratings on the Pain Catastrophizing Scale were a history of falls within the past year, a Health Assessment Questionnaire score >0.5, and smoking habit. Further, patients' subjective symptoms, including patient global assessment minus evaluator global assessment values ≥20 and high tender joint count minus swollen joint counts, were associated with elevated pain catastrophizing. Conclusion: Pain catastrophizing is a major obstacle to achieving remission in RA patients with normal C‐reactive protein levels. Advanced physical disability, smoking habit, and history of falls were associated with pain catastrophizing, in addition to patients' subjective symptoms.